KAJIAN PENGELOLAAN LIMBAH MEDIS COVID-19 DI RUMAH SAKIT - Valentina NFK; Hari Kusnanto Josef; Agus Surono (Journal of Health Service Management, 2023)
Background: Hospitals are one of the largest producers of medical waste. If the medical waste is not managed properly in accordance with applicable standards, it can be dangerous and cause health problems, especially for officers who handle waste, patients, visitors and the community around the hospital.Objective: This study aims to explore the management of COVID-19 medical waste in hospitals, both from input, process and output.Methods: This research is qualitative research with a descriptive case study design. The informants in this study consisted of 15 people who were selected using the purposive sampling method from the internal UGM academic hospital and the surrounding community. Research conducted in May 2022.Results: In the input evaluation it was found that the UGM RSA already had an SOP for handling COVID-19 medical waste, there was already an adequate allocation of funds for the management of COVID-19 medical waste, and human resources had also met the standards. Most of the facilities and infrastructure owned are adequate for processing COVID-19 medical waste. RSA UGM has provided PPE for COVID-19 medical waste collectors but it has not been used optimally. As for process evaluation, sorting and storage have been carried out according to standards. The transportation of COVID-19 medical waste has met the standards but the B3 medical waste TPS has not met the standards. In the output evaluation, none of the respondents experienced health problems related to the management of COVID-19 medical waste.Conclusion: There needs to be improvement in the management of COVID-19 medical waste, especially in the input and process sections.